Analysis of the brazilian potential for electricity generation from photovoltaic solar energy sources and biogas in the context of distributed generation (Research, Society and Development, 2022)
This study aimed to present the current scenario of solar energy and biogas sources in Brazil, analyzing the potential of these sources for the generation of electric energy connected to the grid, in the so-called distributed generation. This topic is relevant, especially because, as of 2012, with the Normative Resolution 482 of the Agência Nacional de Energia Elétrica (ANEEL) - National Electric Energy Agency -, the possibility of generating energy credits was introduced in the market, which is injected into the utility's grid and, subsequently, compensated by the consumer. With the increase in distributed generation, a change in the normative resolution is foreseen, resulting in the need for greater calculations of the economic viability of the undertakings. ANEEL proposed five possible alternatives for changing the compensation of generated credits, where alternatives 4 and 5 would make investments in distributed generation unfeasible. Draft Bill No. 2 of 2019, on the other hand, brings a less pessimistic scenario for the future of distributed generation, which will not make investments unfeasible and will continue to keep the market expanding.